PROSEDUR AUDIT FUNGSI KAS DAN BANK OLEH KAP KANAKA PURADIREDJA, SUHARTONO - Rasmaita Ulina Br Munthe (2020)
Auditing is a methodical process that involves gathering and objectively evaluating evidence pertaining to economic activities and events. The main objective is to determine how well the statements align with the established criteria, while ensuring the competence and independence of the evaluators. Furthermore, the results are communicated to interested parties. The purpose of this thesis report is to analyze the role of cash and bank receipts in PT Xyz's business operations with the aim of achieving company objectives. Data was collected through interviews with senior auditors and documentation. Based on the findings, it can be concluded that PT Xyz's cash and bank receipt function is both effective and efficient, consistently adhering to the company's operational standards.